Pemikiran Fritjof Capra Dalam Ekowisata Hutan Mangrove Desa Adat Kedonganan - Wilantari, Ni Nyoman Ayu; Marisca, Refi (Fakultas Dharma Duta, 2022)
Fritjof Capra is a modern physicist who proposed the ideas about the problem solving of the destruction of natural resources and the widespread occurrence of environmental pollution by humans. This Capra's ideas generated ecoliteracy which now exists in the mangrove forest ecotourism of the Kedonganan Traditional Village as a solution to protecting nature. The holistic systemic theory proposed by Fritjof Capra is in line with the Tri Hita Karana philosophy which represents the harmonious relationship between humans and God, humans and humans and humans natural.